PROSPEK INDUSTRI RUMAH TANGGA SUSU KEDELAI DI KABUPATEN KAMPAR PERIODE 2020-2021 - Nanda Puspita Dian; Harlen Harlen; Mardiana Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study This research aims to determine the prospects for soy milk as a home industry for soy milk in Kampar Regency and to examine the problems or obstacles faced in running a soy milk business in Kampar Regency. The population in this study are all business actors who sell and produce soy milk in Kampar Regency. There are 5 business actors. The method used in this study uses a feasibility test, to conduct a review of the feasibility aspects that examine financial and non-financial aspects. In the non-financial aspect through a review of the market aspect, as well as the financial aspect through a review of financial feasibility by calculating the Net Present Value (NPV), B/C Ratio, Internal Rate of Return (IRR) and Payback Period (PP). The results of this study indicate that the non-financial aspects reviewed in the home industry of soy milk in Kampar Regency have prospects and are feasible to be developed, as well as assessing the financial aspects through feasibility calculations showing NPV = 52,327,985 > 0, the value of B/C Ratio 2, 31 > 1, IRR 56.83% > 12% and PP value for 1 year 6 months. From these calculations, it can be seen that the soy milk industry in Kampar Regency has prospects and is feasible to be developed. .Keywords: Prospect, Feasibility Study and soy milk